Optimal redistributive tax and education policies in general equilibrium - Bas Jacobs (Center for Economic Studies and ifo Institute (CESifo), 2007)
Should a redistributive government optimally subsidize education to provoke a reduction in the skill premium through general equilibrium effects on wages? To answer this question, this paper studies optimal linear and non-linear redistributive income taxes and education subsidies in two-type models with endogenous human capital formation, endogenous labor supply, and endogenous wage rates. Under optimal linear policies, education should not be subsidized so as to reduce the skill premium. Linear income taxes are distributionally equivalent to (negative) linear education subsidies, but linear taxes do not distort investment in human capital, whether general equilibrium effects are present or not. If skilled labor supply is more elastic than unskilled labor supply, optimal redistributive linear income taxes are lowered as the distributional gains of linear taxes are offset by a rise in the skill premium. Moreover, the optimal linear income tax may even become negative if general equilibrium effects are sufficiently strong. Under non-linear taxation, governments can directly steer the skill premium by exploiting non-linearities in the policy schedules. At the top, the optimal marginal income tax rate is negative, and the optimal marginal education subsidy is positive. At the bottom, the optimal marginal income tax rate is positive, and education is optimally taxed at the margin. Hence, optimal non-linear tax and education policies compress wage differentials, which contributes to redistribution. Simulations show that the top rate and marginal education subsidies are close to zero for a wide range of plausible parameters. Only when high-ability and low-ability workers are rather poor substitutes in production, marginal education subsidies on the high type and marginal education taxes on the low type substantially differ from zero.
Keywords: H2; H5; I2; J2; 330; human capital; general equilibrium; education subsidies; optimal taxation; direct and indirect redistribution; Humankapital; Optimale Besteuerung; Bildungsinvestition; Einkommensteuer; Steuerinzidenz; Allgemeines Gleichgewicht; Theorie